Variability of some morphological and physiological features in mountain conditions in Peru - Stolarczyk, Henryk (Anthropological Review, 1986)
Analysed material gathering 105 individuals (63 men and 42 women) was collected in the year 1978 in Puno during anthropological examination of academic youth of local university. This material consists of a great deal of representatives of tribes Aymara and Quechua living in region of lake Uticaca. The measurements of physical features were taken as follow: stature, g-op, eu-eu, mss-mss,fi-ft, zy-zy, go-go, tr-gn, n-gn, n-sio, n-sn, ai-ai. The cephaloscopic data include pigmentation of eyes, hairs, skin and lips, form of eyelid and hairs, profile of face and nose. Moreover some physiological characters, such as blood pressure (systolic and diastolic), pulse before and after effort, girth of thorax during aspiration, rest and expiration; and muscular strenght of hands were registered. The comparison of physical characters of both Indian series indicates above all to greater facial dimensions of Aymara men and women than Quechua. Some dependence between altitude (above sea level) of birthplace and dimensions of thorax girth were confirmed. Female Peruvian students in comparison with Polish student girls evidence to many statistically significant differences in majority of features. Striking great difference in stature in favor of Polish girls should be explained mostly as a modifying influence of natural environment (a harsh existential conditions in Puno). Student girls from Puno have an advantage over Polish students in size of thorax girth, what is connected with their pyknoidal body habit. Polish girls are characterized by higher index of thorax mobility. Moreover the systolic blood pressure as well as pulse of Peruvian student girls is lower than in Polish series. Polish girls characterize greater than in Peruvian students muscular strenght.